EFECTO DE LA FÉRULA OCLUSAL EN EL DOLOR Y EL ESPACIO ARTICULAR EN PACIENTES CON TRASTORNOS TEMPOROMANDIBULARES. ESTUDIO DE SERIE DE CASOS - Pares-Ballasco, Jesús Giancarlo (2025)
Introduction: Temporomandibular disorders (TMD) affect the temporomandibular joint and masticatory muscles. The stabilization occlusal splint (SOS) is a conventional treatment; however, evidence regarding its effects on perceived pain and temporomandibular joint space is limited. Objective: To describe changes in perceived pain and temporomandibular joint spaces in a series of patients with TMD treated with SOS. Methods: Thirteen patients diagnosed with TMD and treated at a hospital were included. Pain intensity was recorded using a visual analog scale (VAS) before and after 30 days of continuous use of the FOE. Using cone beam computed tomography in sagittal and coronal sections, degenerative condylar signs were identified and joint spaces (anterior, superior, posterior, medial, and lateral) were measured before and after the installation of the SOS. Results: The mean age was 26.23 ± 13.94 years, with 69.23% being women. Pain intensity decreased significantly from 6.15 ± 1.82 to 3.62 ± 2.06 (p< 0.001), with the reduction being significant only in women (pand right medial spaces (p< 0.05). Conclusion: The use of SOS in patients with TMD showed a significant reduction in perceived pain and immediate changes in temporomandibular joint spaces.